Idealism versus realism: Performance of Islamic financial institutions in the light of Maqasid-Al Shari'ah - Hassan, Rusni; Salman, Syed Ahmad; Yusoff, Adnan (International Business Information Management Association (IBIMA), 2018)
Shari’ah compliance is the main pushing factor to revitalize the concept of Islamic teaching in the commercial world by emerging Islamic finance industries. This unique compliance is the fundamental distinguishing factor between Islamic and conventional finance. The vision of Islamic finance is to avoid involving in Shari’ah prohibited elements such as interest, uncertainty, gambling and prohibited investments which are currently practiced by the conventional finance industry. These elements are prohibited clearly in the primary sources of Shari’ah, i.e. the Quran and Sunnah. Considering the prohibitions of conventional finance from Islamic perspective, Shari’ah scholars have come out with an alternative solution by introducing Islamic finance. Consequently, there is a tremendous growth of Islamic finance proven by wide-spread subscription of the Islamic finance products and services in both Muslim and non-Muslim countries. However, despite its growth, Islamic finance is not totally free from criticisms that its practice does not meet the ultimate objective of its establishment, i.e. realization of benefit to mankind in this world and Hereafter. In order to achieve this objectives of Shari’ah (maqasid al-Shariah) Islamic financial institutions must aim to provide socioeconomically fair products and services and avoid all the items prohibited by the Shari’ah. Ideally, it should be taking care of public interest and social justice while making profits for the shareholders and investors. If Islamic finance complies with Maqasid Al- Shari’ah, there should not be any undesirable issues against the practices of Islamic finance. However, due to the existence of unfavorable issues, it is timely to revisit the historical practices of Islamic finance so that these past events can be used as lessons for the betterment of Islamic finance in the future. Thus, the main objective of this proposed research is to examine to what extent the Islamic finance sector meets Maqasid Al- Shari’ah.